La sensibilité des larves de pectinidés aux conditions d’élevage : le flux ouvert comme alternative aux mortalités massives - Holbach, Marine (Université de Bretagne Occidentale, 2014)
In many countries, aquaculture of pectinids depends on the success of artificial spat production in hatchery. This production is always unpredictable due to the variability of hatching rate and larval survival. Flow-through larval rearing systems were developed in Norway for the King scallop Pecten maximus and showed promising results. Unfortunately the system needs to be optimized since the larval yields and the densities used are still relatively low. In France, a small-scale (5 L) and high-density (≤ 300 larva mL-1) flow-through larval rearing system was successfully developed for oysters. First trials in such system and in similar conditions with P. maximus failed as we registered slower growth and high mortality rate in only a few days. It is known that pectinids larvae are more sensitive to environmental conditions than the oyster Crassostrea gigas, for example. Nowadays, it is important to identify and to understand the phenomena disturbing larval development in flow-through system to improve larval quality and production yields. In this context, this thesis focuses on (1) controlling the sanitary quality of the early life stage of P. maximus and (2) understanding the sensitivity of larvae in flow-through larval rearing. This document is divided into 3 chapters based on 4 experiments. First, we verified the influence of sediment used during P. maximus broodstock conditioning. This work has shown that using broodstock conditioning without sediment could reduce contamination of gametes and D-larvae by Vibrio. Furthermore, both treatments led to similar fatty acids profiles in oocytes and resulting larvae, suggesting that broodstock conditioning was physiologically similar with or without sediment. The larvae obtained from broodstocks conditioned without sediment had the highest survival rates when reared in a static system. Secondly, we tried to determine the influence of aeration on larval physiology. Larval performances and stress index as antioxidant defenses (catalase and superoxide dismutase) and ...